Analysis of Factors Affecting the Motivation of Honorary Teachers in Border Areas - Eligia Monixa Salfarini; Yeremia Niaga Atlantika; Rissa Ayustia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the factors that influence motivation among honorary teachers in border areas. This study also analyzes what factors play the most important role in providing work encouragement to honorarium teachers. This research is a descriptive study using a qualitative approach. The data in this study were obtained through in-depth interviews with honorary teachers who have worked for three years. The data found were organized in files; the files were classified, codified, and converted into text form to be re-analyzed and presented. The results of the study found that the factors that influence motivation in honorary teachers are individual factors, leaders, the work environment, psicological, and future careers. The research shows that future career plans have the most influence on the work motivation of honorarium teachers at the border. It can be seen that all participants claimed to be motivated to continue working well because of the opportunity to become a contract teacher (PPPK) in public schools.